RFID implementation - Brown, Dennis E. (McGraw-Hill, 2007)
This is the only book available to offer in-depth, practical details for implementing an RFID project from start to finish. From Wal-Mart and beyond, RFID (Radio Frequency Identification) is in use everywhere--enabling superior supply-chain management by tracking inventory via microchip-tagged products. RFID Implementation delivers step-by-step instructions for initiating, installing, and managing an RFID rollout